In Vitro Antioxidant Anti-inflammatory and Acute Toxicity Study of Root Extract of Asparagus Racemosus - Ramesh L. Londonkar (Journal of Global Pharma Technology, 2018)
The purpose of the study is to investigate potential of antioxidant, Anti-inflammatory and acute toxicity study of ethanol root extract of Asparagus racemosus Linn (ASR). The antioxidant activities were evaluated using in vitro Ferric reducing power, Free radical scavenging activity by DPPH method, hydroxyl radical scavenging activity, Nitric oxide radical scavenging activity, Super oxide Anion Radical Scavenging Activity and total antioxidant capacity. The anti-inflammatory potential was also evaluated using Hyaluronidase inhibition assay. The effect was compared with a known antioxidant agent (BHA/Ascorbic acid). It was found that the extract at different concentration exhibited a significant dose dependent antioxidant and anti-inflammatory effect. Acute toxicity study was performed in Wistar rat and an OECD guideline 423 was followed, No sign of toxicity was observed after treating with 2000 mg/kg of ASR.Keywords: Asparagus racemosus, Free radical, acute toxicity, Hyaluronidase inhibition.